Co/productive practitioner relations for children with SLCN: an affect inflected agentic frame. Issue 6 (2nd November 2019) - Forbes, Joan; McCartney, Elspeth; McKean, Cristina; Laing, Karen; Cockerill, Maria; Law, James
ABSTRACT: This paper examines how school-based practitioners supporting children with speech, language and communication needs (SLCN) use particular social capital relations. Social capital theory together with selected 'Productive Pedagogies' items, are applied to re-frame and understand the co/production of support for such children. Empirical data from the 'Language for All' study, which investigates SLCN provision in schools in England, are analysed to understand support network social capital. Novel insights on the types and purposes of inter-professional connectedness within SLCN support networks, in particular how relational agency is inflected by affect, are offered.